Ordeal by fire - McPherson, James M. (McGraw-Hill, 2001)
Written by a leading Civil War historian and Pulitzer Prize winner, this text describes the social, economic, political, and ideological conflicts that led to a unique, tragic, and transitional event in American history. The third edition incorporates recent scholarship and addresses renewed areas of interest in the Civil War/Reconstruction era including the motivations and experiences of common soldiers and the role of women in the war effort